Influence of Different Particle Sizes of Sediments on the Lower Reaches of the Basin and its Significance in the Liao River Governance - Chen Yang (Nature Environment and Pollution Technology, 2023)
Based on the sand volume and sedimentation volume data for different particle size (PS) groups, the relationship between the annual scouring and silting amount of the Juliu River-Liujianfang section and the yearly sediment volume entering the downstream river channel was established. The critical values of sediment storage and release for the downstream river channel were obtained. It was found to decrease with an increase in the sediment particle size. The correlation coefficient between the annual scouring and silting amount of the Juliu River-Liujianfang section and the annual sediment volume entering the downstream river channel increased with the coarsening of sediment PS. It indicated that the sediment size was proportional to the sediment amount (SA) entering the river channel. As the sediment size increased, the deposition amount increased due to the variation of unit sediment amount. Based on the treatment and achievement of source areas with sediment sizes larger than 0.05 mm, it is significant to concentrate on treatment areas with sediment sizes larger than 0.10 mm.